Analisis Faktor-faktor yang Mempengaruhi Tingkat Pengangguran di Kabupaten Indragiri Hilir Tahun 2011-2020 - Risviyaldi; Dhiani Puteri Fathmadani (Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study aims to examine the effect of employment opportunities, labor force participation rates, and economic growth on unemployment in Indragiri Hilir Regency. This study uses a quantitative methodology approach using secondary data from the Central Statistics Agency of Indragiri Hilir Regency in the form of time series data from 2011-2020. The technique used to collect the data is non-behavioral observation on records. The sample used is data for ten years where the sampling technique uses saturated samples. Meanwhile, to analyze the data, an OLS-based regression technique was used with Eviews 10. From the results of the study, the regression coefficient value of X1 is -15.556, the regression coefficient of X2 is -0.547, and the regression coefficient of X3 is -0.024. While the partial t-statistic of X1 is -3.856, X2 is -11.880, X3 is -0.357, and simultaneously the F count value is 86.357 with F table of 0.000025. Based on the results of this study, it can be concluded that the level of employment opportunities has a significant effect on the unemployment rate, the labor force participation rate has a significant effect on the unemployment rate, economic growth has a significant effect on the unemployment rate and simultaneously the level of employment opportunities, the labor force participation rate, and economic growth have a significant effect on unemployment in Indragiri Hilir Regency.